Heineken: sponsor and promoter of sports event tourism - Silva, Carlos Augusto Barbosa da; Gonçalves, Julia Pereira; Campos, Kauã Dias Ferreira; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2022)
Sponsorship of sporting events consists of an aid or support, so that a contribution is made, whether in money or service, with or without advertising compensation. In sporting events, they can be done through the athletes themselves or in the events, it provides a financial value that will be exchanged for the representation of the sponsor’s brand, and aiming to reach a certain audience. In this context, the main objective of this work is to analyze the contribution of Heineken’s sports sponsorship to the tourism of sports events. The results for the events sponsored by Heineken indicated that the brand is a sponsor of four sporting events: UEFA Champions League, Formula 1 and Formula E, in addition to being a central sponsor of the Rugby Champions League. The results related to the impacts of sporting events on tourism showed that these events stimulate the economy and tourism in the places where they occur, attracting tourists and promoting tourism through flights, accommodation, food and leisure. The work proposes an analysis of the impacts of Heineken’s sponsorship and its position as a promoter of sport events tourism.